Nomes próprios no romance contemporâneo O Berro do Cordeiro em nova York: um estudo onomástico exploratório - Camargo, Amanda Kristensen de (2018)
The inquiries about proper name: its linguistic nature, identifying function, its correlation with the named personality, its motivation/immotivation, connotative face among other questions are as old as the social act of naming. Wishing to review these questions of socionomastic origin and relate them to Literature – as an artisticsocial product and that, therefore, dialogue with the society –, this research, with an onomastic-literary-exploratory nature, proposes a comparison of contemporary fictional nomination related to the society contemporary nomination, highlighting in the continuum of very or little mimetic names related to very or little connotative the linguistic and literary different functions of onomas – anthroponyms, toponyms and pantheonyms – immersed in the hybrid discourse of the contemporary Brazilian romance O berro do Cordeiro em Nova York, by Tereza Albues (1995). Through the onomastic data collect, the contemporary literary corpus selected by us seemed even more onomasticly fruitful then expected initially, fact that allowed the confirmation of the theoretical relevance of its autoficcional aesthetics and hybrid migrant to the enrichment of our considerations, once the performative performance of Tereza, as character-narrator without name and the description of her errands, contributed to a pretty solid material basis that practically instituted the methodology of our analysis. It was noticeable that, as much mimetic as the onomas can initially show up – close to the contemporary society nomination, usually non-motivated etymologically or connotatively –, in the literary discourse, those onomas mostly propose symbolic assertions that exceed the socio-onomastic mimese, mixing up to it. This way, the onomas classification proposed by us is not final, but a continuum in which the names more or less mimetic and more or less connotative are find orthogonally and follow the literary language – equally not final – on its maximum performative degree.